Peningkatan Proses dan Hasil Belajar Peserta Didik Melalui Model Pembelajaran CTL Dalam Pendidikan IPAS Di Sekolah Dasar - Adrian; Megawati; Pitra, Dedek Helida (CV. Master Literasi Indonesia, 2025)
This study aims to analyze the effectiveness of implementing the Contextual Teaching and Learning (CTL) model in improving the learning process and outcomes of Natural and Social Sciences (IPAS) in elementary school students. The method used is Classroom Action Research (CAR) conducted in two cycles, each covering the stages of planning, implementation of actions, observation, and reflection. The research subjects consisted of 12 fifth-grade students at Muhammadiyah Muara Bungo Elementary School, with the researcher acting as the teacher and assisted by two observers. Data were collected using qualitative techniques in the form of observation sheets and quantitative techniques in the form of learning outcome tests. The results showed that the application of CTL was able to improve the implementation of learning and student learning outcomes. Teacher observation increased from 71.42% in cycle I to 84.37% in cycle II, while student observation increased from 58% to 79%. The improvement in student learning outcomes was also significant, from 41.66% in cycle I to 83.33% in cycle II. These findings indicate that the CTL model can be an effective alternative learning strategy to improve the quality of the learning process and academic achievement of students in IPAS subjects. The implications of this study encourage the wider application of CTL as an innovative effort in contextual experience-based learning in elementary schools.